Highly conductive and ultra-durable electronic textiles via covalent immobilization of carbon nanomaterials on cotton fabric. Issue 45 (1st November 2018) - Cui, Junshuo; Zhou, Shuxue
Abstract : Graphene and MWCNTs were firmly immobilized on the fiber surface by covalent networks generated from the condensation of the reactive dispersant. Abstract : Graphene and multi-walled carbon nanotubes (MWCNTs) are promising candidates for the fabrication of flexible electronic textiles (E-textiles) due to their light weight and chemical stability. However, common issues of the carbon-based E-textiles such as low electrical conductivity, poor durability, and tedious fabrication processes still exist at present. In this study, fabrics with low sheet resistance and ultra-durability were fabricated using a simple dip-coating approach. A self-cross-linkable dispersant, possessing several silanol groups, was used for preparing graphene and MWCNTs dispersions. After a dip-coating/drying process, covalent networks were formed across the coating layer, which firmly immobilized graphene and MWCNTs on the fabric surface. Conductive fabrics with a sheet resistance of 33.2 Ω sq −1 and 29.8 Ω sq −1 were obtained using MWCNTs and graphene as carbon nanomaterials, respectively. Their conductivities remained almost unchanged after washing and sonication in water and various organic solvents. The tensile strength of the fabric significantly improved after the incorporation of graphene or MWCNTs on its surface. Excellent stretch sensing and electric heating performances were also revealed for the nanocarbon-coated textiles.